2008
DOI: 10.1111/j.1600-0765.2007.01023.x
|View full text |Cite
|
Sign up to set email alerts
|

Injectable growth/differentiation factor‐5–recombinant human collagen composite induces endochondral ossification via Sry‐related HMG box 9 (Sox9)expression and angiogenesis in murine calvariae

Abstract: These results suggest that rhCI seems to allow the release of rhGDF-5 and that rhGDF-5-rhCI composite induces endochondral ossification via Sox9 expression and angiogenesis in murine calvariae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…On the other hand, these data may also imply that exogenous rhGDF-5 treatment heals defects via classical endochondral ossification, while the defects enhanced with rhBMP-2 may heal through intramembranous ossification. In fact, these observations are supported by a number of reports in the literature where it is demonstrated that bone repairs with exogenous rhGDF-5 treatment initiated endochondral ossification (Erlacher et al 1998b;Bai et al 2004;Kakudo et al 2007;Kadomatsu et al 2008). At the same time, other studies from the literature have reported that chondrogenic and osteogenic lineage pathways in response to rhGDF-5 treatment are dose and carrier dependent (Spiro et .…”
Section: Discussionsupporting
confidence: 75%
“…On the other hand, these data may also imply that exogenous rhGDF-5 treatment heals defects via classical endochondral ossification, while the defects enhanced with rhBMP-2 may heal through intramembranous ossification. In fact, these observations are supported by a number of reports in the literature where it is demonstrated that bone repairs with exogenous rhGDF-5 treatment initiated endochondral ossification (Erlacher et al 1998b;Bai et al 2004;Kakudo et al 2007;Kadomatsu et al 2008). At the same time, other studies from the literature have reported that chondrogenic and osteogenic lineage pathways in response to rhGDF-5 treatment are dose and carrier dependent (Spiro et .…”
Section: Discussionsupporting
confidence: 75%
“…Several studies revealed that GDF-5 plays a pivotal role in a variety of musculoskeletal processes including endochondral ossification [33,34], joint formation [11,35], tendon and ligament maintenance and repair [36,37]. In addition, GDF-5 has been demonstrated to play a role in osteogenesis and ectopic bone formation [12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies suggested that the administration of GDF-5 with suitable carriers induced the formation of tendon-/ligament-like and cartilage/bone-like tissues in some rodents, ruminants and primates [4][5][6]. For bone tissue engineering GDF-5 has been used in combination with scaffolds such as collagen [5,7,8] or mineralized collagen [9] which, however, do not provide any biomechanical stability. Therefore, in a weight bearing situation additional stabilization is required [10].…”
Section: Introductionmentioning
confidence: 97%